Probability distributions of three‐antenna efficiency measurement in a reverberation chamber - Qian Xu; Lei Xing; Yongjiu Zhao; Tianyuan Jia; Yi Huang (IET Microwaves, Antennas & Propagation, 2021)
Abstract Analytical expressions are derived for probability distributions of the three‐antenna efficiency measurement. The probability density function (PDF), the expected value, and the standard deviation are derived analytically. The Mellin transform is used in the PDF derivation to obtain the product of random variables, and the analytical distributions for the measured antenna efficiency are obtained. Measurements are performed to verify the results, which agree well with the analytical expressions.